解:
設數列{an}是等差數列,其公差為d,d≠0,根據等差數列的定義:
an - a(n-1) = d
∴a2- a1= d
a3 - a2 = d
a4 - a3 = d
.....
上述各式相加:
an - a1 = (n-1)d
即:an = a1 + (n-1)d
令Sn = a1 + a2 +.....+ an
根據an = a1 + (n-1)d,易知,
a(n-k) + a(k+1) = a1+(n-k-1)d+a1+kd
=2a1+(n-1)d ,其中k = 0,1,2,3...n-1
當n固定不變時,上式為定值
因此:
Sn = a1 + a2 + a3 +.....+ an
Sn = an + a(n-1)+........+ a1
上式相加:
2Sn= n[2a1+(n-1)d]
Sn=na1 + n(n-1)d/2
根據an = a1 + (n-1)d
上式也可寫成:
Sn =n(a1+an)/2
解:
設數列{an}是等差數列,其公差為d,d≠0,根據等差數列的定義:
an - a(n-1) = d
∴a2- a1= d
a3 - a2 = d
a4 - a3 = d
.....
an - a(n-1) = d
上述各式相加:
an - a1 = (n-1)d
即:an = a1 + (n-1)d
令Sn = a1 + a2 +.....+ an
根據an = a1 + (n-1)d,易知,
a(n-k) + a(k+1) = a1+(n-k-1)d+a1+kd
=2a1+(n-1)d ,其中k = 0,1,2,3...n-1
當n固定不變時,上式為定值
因此:
Sn = a1 + a2 + a3 +.....+ an
Sn = an + a(n-1)+........+ a1
上式相加:
2Sn= n[2a1+(n-1)d]
Sn=na1 + n(n-1)d/2
根據an = a1 + (n-1)d
上式也可寫成:
Sn =n(a1+an)/2